Attitude and position controller design and implementation for a quadrotor. (22nd May 2017) - Mardan, Maziar; Esfandiari, Masoumeh; Sepehri, Nariman
The performance of quadrotors can be significantly disturbed in the presence of wind. In this article, a simple-to-implement attitude controller is proposed to render a robust and accurate trajectory tracking in the presence of disturbance and model uncertainties. The attitude controller design is based on quantitative feedback theory. A fuzzy logic controller is further employed to provide a satisfactory position trajectory tracking for the quadrotor. The performances of the controllers, in terms of disturbance rejection and trajectory tracking, are experimentally studied. Finally, a flight scenario is performed that compares the performance of the designed quantitative feedback theory-fuzzy control scheme with the ArduCopter controller.